2012
DOI: 10.2135/cropsci2012.01.0020
|View full text |Cite
|
Sign up to set email alerts
|

Extra Long Staple Upland Cotton for the Production of Superior Yarns

Abstract: Cotton {Gossypium spp.) fibers are produced primarily by G. hirsutum L., upland, and G. barbadense L., pima, or Extra Long Staple (ELS). Two ELS upland lines, developed by Texas AgriLife Research, along with 'FiberMax 832LL' (FM 832) and 'DPL Pima HTO' (Pima HTO), were grown in a randomized complete block design at College Station, TX, during 2007 and 2008. Subplots of spindle-harvested seedcotton were ginned on a saw gin or roller gin with appropriate lint cleaning. High-volume instrument (HVI) and Advanced F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
(18 reference statements)
5
10
2
Order By: Relevance
“…It then calculates a centerline for each seed, which serves as an axis for the program to apply three different cross-sectional shapes to create three different three-dimensional surface area estimates of the seed. Neps, entanglements of immature fibers or fibers with minute trash, followed the same trend as Joy et al (2012) reported and all genotypes in this study exhibited mature fibers as indicated by MR. TAM B182-33 ELS, B182-34 ELS, and Pima HTO had significantly larger seeds than the two upland cultivars, averaging 123 and 104 mm 2 per seed, respectively (Table 3). All surface area per seed values reported herein were based on a circular cross section.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…It then calculates a centerline for each seed, which serves as an axis for the program to apply three different cross-sectional shapes to create three different three-dimensional surface area estimates of the seed. Neps, entanglements of immature fibers or fibers with minute trash, followed the same trend as Joy et al (2012) reported and all genotypes in this study exhibited mature fibers as indicated by MR. TAM B182-33 ELS, B182-34 ELS, and Pima HTO had significantly larger seeds than the two upland cultivars, averaging 123 and 104 mm 2 per seed, respectively (Table 3). All surface area per seed values reported herein were based on a circular cross section.…”
Section: Resultssupporting
confidence: 84%
“…Multiplying by 1000 converts mg km -1 (Fn) m, while Ln must be converted from inches to m by multiplying by 0.0254. The quotient of sample weight divided by fiber density is total fiber length and the quotient of total fiber length divided by the average individual Joy et al (2012). The AFIS fineness also was as expected with the ELS experimental upland lines exhibiting finer fibers (p < 0.05) than Fibermax 832 or Phytogen PSC 355, but not finer than Pima HTO.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…These results can be attributed to the edaphoclimatic differences between the sites (Table 1) and indicate the need for applying stability and adaptability methods to recommend the best genotypes. Similar results were obtained by Ng et al (2013), Joy et al (2012), and Campbell and Jones (2005), who also observed significant G x E interactions for the FY and FL traits.…”
Section: Regression Model Proposed By Eberhart and Russellsupporting
confidence: 87%
“…The remaining 12 genotypes included in this study were Texas A&M AgriLife strains developed for exceptional UHML, eight of which were released in 2009 (Smith et al, 2009). All experimental strains were selected as a part of the Cotton Improvement Laboratory efforts to develop upland cotton with UHML and strength exceeding that of all current upland cotton cultivars in the United States (Smith et al, 2008(Smith et al, , 2009Joy et al, 2010Joy et al, , 2012Gregory et al, 2012 (Table 1). All production practices were normal for the locale, including boll weevil (Anthonomus grandis) eradication protocol.…”
mentioning
confidence: 99%